Invasive Pressure Monitoring Saves from Tuberculous Meningitis with Fulminant Generalized Brain Edema - Trendelenburg, George; Jussen, Daniel; Grimmer, Steffen; Jakob, wibke; Hiemann, Nicola E.; Horn, Peter (Frontiers in Neurology, 2011)
We report a 57-year old female patient with a rapid and dramatic dynamic of whole brain edema caused by tuberculous meningitis. After initiation of tuberculostatic medication, general condition of the patient worsened and finally she was intubated due to a progredient loss of consciousness and respiratory insufficiency. Repeated cerebral computer tomography (CCT) revealed a global brain edema with slit ventricles and a dramatic progress of generalized brain swelling. Highly interesting, a rapid expanded regime of brain pressure monitoring and treatment according to a neurosurgical intensive standard ICP/CPP management protocol, which was complemented by the tuberculostatic therapy and high dose steroid application, dramatically improved the general conditions, so that the patient is now in a general condition which corresponds that before the occurrence of tuberculous meningitis. Thus, it is mandatory in situations with a rapid progressive brain swelling caused by bacterial meningitis to consider an intensified cerebral monitoring and stratified treatment protocol in order to avoid the devasting effects of a long lasting increase in intracranical pressure.